SECURITIES MARKET IN FINANCIAL SUPPORT OF MONETARY RELATIONS - Levandivskyi, O.T.; Krykhovetska, Z.M.; Matskiv , V.V. (The actual problems of regional economy development, 2022)
The article considers the current state of the securities market within the financial support of monetary relations. The main levers of support for the domestic securities market have been identified. Emphasis is placed on the further development of monetary relations through the use of securities as tools to attract investment to restore the destroyed infrastructure of the country. It is emphasized that the further development of the securities market depends on the development of the country's economic potential. Regulations are analyzed. Approaches to securities circulation are considered. The influence of digitalization on the emergence of innovative financial instruments is revealed. It is emphasized that the circulation of bank certificates of deposit will promote the development of the securities market and monetary relations. The issuance of infrastructure bonds and the issuance of green bonds will help support the country's greening. A review of innovative financial instruments of individual countries. The peculiarities of the functioning of the securities market outside the country are considered, the use of alternative financial instruments of the world's leading countries is shown. The mechanism of project financing is outlined in view of the emergence of alternative financial instruments. The directions of application of the mechanism of project financing in the national economy are substantiated. Based on the experience of the world's leading countries, the priorities of the securities market development have been identified, taking into account the specifics of the functioning of the monetary system and the economy of Ukraine as a whole. Emphasis is placed on the liquidity of modern financial instruments.It is proposed to introduce a number of tax benefits related to the circulation of certain financial instruments. Emphasis is placed on the need to create tools to guarantee the protection of foreign investment. Given the experience of countries around the world in organizing and using alternative financial instruments to raise funds in various sectors of the economy shows that their effective application is possible in the development and implementation of a single integrated state policy harmonized with international law, taking into account best practices national conditions.